2015
DOI: 10.1080/10615806.2015.1061123
|View full text |Cite
|
Sign up to set email alerts
|

Work overload, burnout, and psychological ill-health symptoms: a three-wave mediation model of the employee health impairment process

Abstract: The results provided supportive evidence for an "indirect-only" mediation effect, for burnout's causal mediation mechanism in the health impairment process between work overload and psychological ill-health symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 55 publications
4
49
0
2
Order By: Relevance
“…This result is in alignment with previous studies which found work overload to predict burnout (Bakker & Demerouti, 2007; De Beer et al, 2016). The reality of high workloads and the associated risks causes various challenges for organizations as the current economic climate necessitates a lot of organizations to expect employees to deliver greater outputs with fewer resources (Evenstad, 2015) to ensure the profitability and sustainability of the business.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This result is in alignment with previous studies which found work overload to predict burnout (Bakker & Demerouti, 2007; De Beer et al, 2016). The reality of high workloads and the associated risks causes various challenges for organizations as the current economic climate necessitates a lot of organizations to expect employees to deliver greater outputs with fewer resources (Evenstad, 2015) to ensure the profitability and sustainability of the business.…”
Section: Discussionsupporting
confidence: 93%
“…Strong empirical evidence exists in the literature to support the view that excessive job demands are a key predictor of burnout (Alarcon, 2011; Bakker, Demerouti, & Verbeke, 2004; De Beer et al, 2016; Demerouti, Bakker, Nachreiner, & Schaufeli, 2001). Participants viewed change management as a form of job demand and experienced it through a lack of communication, uncertainty about why changes were made, and changes in leadership.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations